1994
DOI: 10.1117/12.176038
|View full text |Cite
|
Sign up to set email alerts
|

<title>PUEO: the Canada-France-Hawaii Telescope adaptive optics bonnette I: system description</title>

Abstract: The Canada.Fraxxe-Hawajj Telescope (GHT) is developing an Adaptive Optics Instrument Adaptor for general use at its 3.6 m telescope. It consists of a 19 electrode, bimcrph deformable mirror (1:6:12) used with a 19 sub-aperture, curvature wavefront sensor. The wavefront sensor optical gain is controlled by the amplitude of a vibrating membrane mirror, which produces a defocus in t1 pupil plane. The tip-tilt correction is accomplished separately from the high order correction by tI f/19.6 reimaging mirror of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Véran et al (1997) have been the first to develop such a PSF reconstruction algorithm. Implemented on the CFHT curvature sensing AO system PUEO (Arsenault et al 1994), it has been routinely delivering reconstructed on-axis PSFs for more than 8 years now. A first attempt to transpose this algorithm to the Shack-Hartmann (SH) wavefront sensor has been undertaken by Harder & Chelli (2000).…”
Section: Introductionmentioning
confidence: 99%
“…Véran et al (1997) have been the first to develop such a PSF reconstruction algorithm. Implemented on the CFHT curvature sensing AO system PUEO (Arsenault et al 1994), it has been routinely delivering reconstructed on-axis PSFs for more than 8 years now. A first attempt to transpose this algorithm to the Shack-Hartmann (SH) wavefront sensor has been undertaken by Harder & Chelli (2000).…”
Section: Introductionmentioning
confidence: 99%
“…The first bimorph from CILAS operating on the sky was developed for the AO system known as "PUEO" [2]. It was installed on the 3.6-meter Canada-France-Hawaii Telescope (CFHT), located near the summit of Mauna Kea on Hawaii's Big Island at an altitude of 4,204 meters.…”
Section: B Heritage Through Ground-based Telescopesmentioning
confidence: 99%
“…The first major success of this collaboration was obtained in 1989 with the first light of COME-ON (Cge, Observatoire de Meudon, Eso, ONera). The results obtained with this Adaptive Optics (AO) prototype constituted the first demonstration in astronomy of atmospheric turbulence real-time correction [2]. Such as many other AO systems from ESO (European Southern Observatory), this first system was equipped with a piezoelectric deformable mirror designed and manufactured by CILAS (formerly CGE).…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Véran et al (1997) have demonstrated that AO allows one to derive the PSF from wavefront-related data delivered by the AO RTC. They have been the first to develop such a PSF reconstruction algorithm and to implement it on an AO system: PUEO, the CFHT curvature AO system (Arsenault et al, 1994). Since then, the algorithm is routinely used to provide astronomers with the (on-axis) PSF associated to their observations.…”
Section: Introductionmentioning
confidence: 99%